GLIS3 and Thyroid: A Pleiotropic Candidate Gene for Congenital Hypothyroidism - Rurale, Giuditta; Persani, Luca; Marelli, Federica (Frontiers in Endocrinology, 2018)
Variations in the transcription factor Gli-similar 3 (GLIS3) gene have been associated to variable congenital endocrine defects, including both morphogenetic and functional thyroid alterations. The generation of Glis3 knockout mice demonstrated a relevant role for GLIS3 in thyroid hormone biosynthesis and postnatal thyroid gland growth, acting down-stream of TSH/TSHR system. However, the pathophysiological role of this transcription factor during the embryonic thyroid development remains unexplored. In this manuscript, we will provide an overview of the current knowledge on GLIS3 function during development. As a perspective, we will present preliminary evidence in the zebrafish model in support of a potential role for this pleiotropic transcription factor in the early stages of thyroid gland development.